2018
DOI: 10.3389/fpsyg.2018.00238
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition, Updating Working Memory, and Shifting Predict Reading Disability Symptoms in a Hybrid Model: Project KIDS

Abstract: Recent achievement research suggests that executive function (EF), a set of regulatory processes that control both thought and action necessary for goal-directed behavior, is related to typical and atypical reading performance. This project examines the relation of EF, as measured by its components, Inhibition, Updating Working Memory, and Shifting, with a hybrid model of reading disability (RD). Our sample included 420 children who participated in a broader intervention project when they were in KG-third grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 98 publications
0
25
0
4
Order By: Relevance
“…The authors actually found that reading and math skills were less related in transparent compared to opaque languages and that they were more related in timed vs. untimed reading and math tasks. Evidence of literacy and numeracy interrelations opens the way to more complex reflections regarding the possible role of domain-general skills, with particular attention to the role of executive functions (EFs) as suggested by previous studies, that found relationships between EFs and academic achievement (Best et al, 2011;Chiappe & MacDonald, 2005), as well as with literacy (Cummine et al, 2018;Daucourt et al, 2018), numeracy (Mazzocco & Kover, 2007), or both (e.g., Davidse et al, 2014).…”
Section: Cognitive Predictors Of Early Literacy and Numeracy Skillsmentioning
confidence: 97%
“…The authors actually found that reading and math skills were less related in transparent compared to opaque languages and that they were more related in timed vs. untimed reading and math tasks. Evidence of literacy and numeracy interrelations opens the way to more complex reflections regarding the possible role of domain-general skills, with particular attention to the role of executive functions (EFs) as suggested by previous studies, that found relationships between EFs and academic achievement (Best et al, 2011;Chiappe & MacDonald, 2005), as well as with literacy (Cummine et al, 2018;Daucourt et al, 2018), numeracy (Mazzocco & Kover, 2007), or both (e.g., Davidse et al, 2014).…”
Section: Cognitive Predictors Of Early Literacy and Numeracy Skillsmentioning
confidence: 97%
“…For example, to examine if students’ scores on executive functioning measures predicted reading disabilities, Daucourt and colleagues (2018) combined eight different data sets. The original data sets included student achievement data from reading intervention studies.…”
Section: Open Science In Educational Sciencesmentioning
confidence: 99%
“…In this particular example, Daucourt and colleagues (2018) were able to capitalize on existing data to run a relatively low-cost study. By using the already collected reading achievement data from the original intervention studies, they avoided having to unnecessarily spend resources on assessments and were able to append these data with the parent questionnaire.…”
Section: Open Science In Educational Sciencesmentioning
confidence: 99%
“…Evalúa los problemas en 8 escalas de FE que se agrupan en dos índices (regulación conductual y metacognición) y una puntuación total. Daucourt, Schatschneider, Connor, Al Otaiba y Hart (2018) analizaron la relación de tres de las escalas incluidas en el cuestionario (MT, inhibición y cambio) con un modelo de disfunción de acceso al léxico en una muestra de 420 niños, encontrado una clara relación entre las mismas. Similares son los resultados obtenidos utilizando otros instrumentos de evaluación ecológica del FE, como el Childhood Executive Functioning Inventory (CHEXI; Thorell y Nyberg, 2008).…”
Section: Introductionunclassified